The atomic power station of new generation in Ukraine - Коцуба, Олександр Леонідович; Василик, Дмитро Олександрович (Eastern-European Journal of Enterprise Technologies, 2012)
The comparative characteristics of the project B392 is shown. This project is a product of evolutionary development draft V320. A comparison of the main equipment projects and systems of protection that are aimed at improving safety and efficiency is being made